ARTIFICIAL INTELLIGENCE IN MANAGEMENT: OPPORTUNITIES FOR OPTIMIZING BUSINESS PROCESSES AND RISK MANAGEMENT - DVORNYK, Iryna; SHEVEL, Yaroslav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines contemporary transformational processes in management caused by rapid digitization, globalization, and the growing spread and popularization of technologies related to artificial intelligence in the business environment and society in general. It is argued that traditional management approaches based on the intuitive experience of managers and linear decision-making models are gradually losing their effectiveness in the context of information overload and the need to process large amounts of data. Particular attention is paid to the analysis of the possibilities of autonomous application of artificial intelligence technologies in general, in management business processes, in particular in RPA-based automation, strategic planning, risk management, and human resource management. Based on the positions of contemporary scientific literature (which currently mostly considers AI technology as an assisting instrument rather than an autonomous part of the management processes) and current statistics on the implementation of AI, it has been proven that the integration of algorithmic systems into management can significantly improve the accuracy of analytics, the effectiveness of forecasting, and the adaptability of enterprises to the dynamic conditions of the digital economy. At the same time, a number of risks associated with AI’s dependence on data quality, potential algorithm bias, and limited ability to take into account unpredictable factors have been identified and analyzed. It was concluded that the most promising direction for development is the formation of a hybrid management model that combines algorithmic accuracy and speed of information processing with human intuition, creativity, and adaptability, which can effectively negate the discovered risks to produce novel management systems, which can successfully answer the new challenges posed by the digital-based global economy.